Bad loans Problem in Indian PSU Banks: Impact of Selected Bank Specific Variables on NPA: - (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Banks play very crucial role for the economic growth of a nation. Banks do not only deal with acceptance of deposits and extension of credit facilities but they also accelerate the growth engine of the nation. Indian banking system is not different in this context as they also extend the credit and accept deposits as banks of the other nations. Banks primarily deals in extension of credit through lending in various and diverse sectors belong to economy as per the lending policy and sometimes in meeting of the socio economic purposes of the country. Lending always carries a risk, widely known as credit risk. Credit risk arises when borrower of the advancecredit is unable to make repayment of such loan in form of principle or interest or both in the specified time period according to the guidelines for lending determined by the Reserve Bank of India. These loans which do possess magnified proportion of such risk are usually termed as bad loans. Bad loan problem has radically increased in Indian banking system during last couple of years. Though the Bad loans which is also articulated as NPA is allied with whole banking structure of the nation but the extent of the problem is more significant with Indian PSU Banks. An attempt has been made in this paper to explicate the problem of bad loan problem of Indian Public Sector Banks. Further, attempt has made in the present paper to investigate the influence of particular variables belong to Indian PSU banks such as advances, bank borrowings, reserves surplus and total assets on Non-Performing Assets (Popularly known as NPA) of Public Sector banks in India. Movement of NPA belong to Indian PSU banks have also been analysed with the help of bar diagrams during 2003 to 2016. Study concludes with several recommendationssuggestions to cope up with the problem.